2016
DOI: 10.20960/nh.315
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake according to hydration status in 9-10 year-old soccer players

Abstract: Introduction: Children have an increased risk of voluntary dehydration especially during physical activity which may increase the risk of non-compensating water losses. Objectives: The aim of this study was to assess the hydration status and its relation to food intake in a children group of soccer players. Method: A sample of 36 boys aged 9-10 years was included in this study; 30 completed a 24 h urine collection. Participants completed a 24 h urine collection; a 24 hours food recall corresponding to the day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
2
1
0
1
Order By: Relevance
“…The 24-h urine osmolality result was similar to that in other studies, in schoolchildren, as performed using the same methodology in different countries such as France [38], Egypt [39, 40], Greece [41], Portugal [42] and the United States [43].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The 24-h urine osmolality result was similar to that in other studies, in schoolchildren, as performed using the same methodology in different countries such as France [38], Egypt [39, 40], Greece [41], Portugal [42] and the United States [43].…”
Section: Discussionsupporting
confidence: 83%
“…We found that males had higher osmolality values than females. This result has been supported by several studies such as Ebner & Manz [44] in German schoolchildren (4–14 years old) from the DONALD study, Kavouras et al [41] (Greece schoolchildren from 9–13 years old), Bonnet et al [38] (French schoolchildren, 9–11 years old) and in Portuguese schoolchildren by Rodríguez et al [42] (9–10 years old) and Padrao et al [41] (7–11 years old). There are some factors that could explain these disparities between males and females.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Mas a hipohidração humana pode ser provocada pelo uso de restrição de água, exercício prolongado, estresse térmico, administração diurética, ou uma combinação de métodos (JOHNSON EC, 2016; WATSON JC e FARQUHAR WB., 2019) Os efeitos mais proeminentes do desequilíbrio da água corporal são a percepção da sede, assumindo o consumo subsequente de água, e a concentração circulante de hormônios como a vasopressina arginina (AVP) e aqueles relacionados ao sistema de renina-angiotensina-aldosterona. Essas alterações no estado de hidratação dos indivíduos influenciam o seu bem-estar e podem prejudicar a sua saúde, sendo que a desidratação se associa ao declínio funcional, comprometendo a performance cognitiva e a capacidade motora, e pode ser fatal (JOHNSON EC, 2016; RODRIGUEZ L, et al, 2016).…”
Section: Introductionunclassified